Wnt repertoire and developmental expression patterns in the crustacean Thamnocephalus platyurus. Issue 5 (3rd October 2016) - Constantinou, Savvas J.; Pace, Ryan M.; Stangl, A. J.; Nagy, Lisa M.; Williams, Terri A.
SUMMARY: Wnt genes are a family of conserved glycoprotein ligands that play a role in a wide variety of cell and developmental processes, from cell proliferation to axis elongation. There are 13 Wnt subfamilies found among metazoans. Eleven of these appear conserved in arthropods with a pattern of loss during evolution of as many as six subfamilies among hexapods. Here we report on Wnt genes in the branchiopod crustacean, Thamnocephalus platyurus, including the first documentation of the expression of the complete Wnt gene family in a crustacean. Our results suggest fewer Wnt genes were retained in Thamnocephalus than in the related crustacean, Daphnia, although the Thamnocephalus Wnt repertoire is larger than that found in insects. We also find an intriguing pattern of staggered expression of Wnts —an anterior‐posterior stagger within the posterior growth zone and a dorsal‐ventral stagger in the developing segments—suggesting a potential for subfunctionalization of Wnts in these regions.